Population fluctuation of Anastrepha spp. in Creole mango in four locations in Vinces, Ecuador - Meza , Jorge; Rodríguez, Alexander; Mendoza, Edwin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Among species in the genus Anastrepha we find several key pests belonging to fruit crops of quarantine importance established by importing countries. The knowledge of population fluctuation of these pests, in certain areas is a starting point for designing control strategies. The population fluctuation of fruit flies was evaluated in four localities of the Vinces country, Los Ríos province (La Americana, Santa Martha, Primavera and Pavana). For this purpose, we used McPhail traps with hydrolyzed protein bait, and placed three traps per site into trees that are recognized hosts of fruit flies. Traps were reviewed weekly, and fly.trap‐1.day‐1 (FTD) index was determined, outcomes were correlated with climatic variables. Results show that population peaked in December, FTD was 5,94, temperature was 27,40°C and relative humidity 78%. We found a positive moderate correlation between the captured insects and the temperature expressed in °C, with a correlative value r = 0,61 and a negative correlation with relative humidity (r = ‐0.64). Anastrepha fraterculus (Wiedemann) was the most conspicuous with 3111 specimens, 1055 were found in La Americana, the location with the highest infestation.